FIQH PERSPECTIVES ON HYGIENE AND ITS RELEVANCE FOR HEALTH - Pulungan, Sahmiar; Sarudin, Sarudin (JURNAL ILMU SYARIAH, 2023)
Keeping health is the most important element in medicine in the view of Islamic law. Health is a very big gift from Allah, therefore, Islam places great emphasis on humans taking care of their health as well as taking care of every cause that can suffer from illness. The purpose of this study is to describe the views of fiqh scholars on cleanliness and what is its relevance to health. This research is library research and field research with qualitative methods. Sources of data come from library studies in the form of Al-Qur'an, hadith, books, journals. Data analysis was done by three steps, they are data reduction, applying data and conclusion. The results of this study are the views of fiqh scholars that Islam prioritizes a healthy lifestyle, such as advice on maintaining health, cleanliness, diet, maintaining honor from heinous acts, abstaining from consuming khamr from various addictive substances, and so on. In addition to physical health, Islam also pays high attention to mental health. Mental health is a branch of psychology.